Genetic diversity and stability in aromatic rice (Oryza sativa) - MISHRA, D; DASH, S K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy (wet) season of 1991-94 to study genetic diversity and stability in 10 genotypes of aromatic rice (Oryza sativa L.). Pooled data of 9 quantitative characters, viz days to 50% flowering, plant height, tillers/hill, ears/hill, panicle length, grains/panicle, chaffs/panicle, 100-grain weight and grain yield, for 4 environments were analysed, and 4 clusters of genotypes were formed on the basis of D2 statistics. Pooled analysis showed highly significant differences due ,to genotypes, environments and genotype X environment interaction for all the characters. On the basis of stability parambter (b1 and S2di) the genotype' Kasturi' was found stable for yield with higher mean yield and 'ORP 665-7' was found stable for 4 yield-attributing characters with higher mean yield. On the basis of D2 analysis and stability, crossing among the selected genotypes of cluster II ('ORP 665-7' and 'Kasturi') with the genotype of cluster IV ('Badena') was found useful to recombine gene for stability and higher yield.